Pengaruh Pengungkapan Corporate Social Responsibility Pada Nilai Perusahaan Dengan Good Corporate Governance Sebagai Pemoderasi - Vira, Ayu Nikita; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 26 No 2 (2019), 2019)
One thing that can encourage companies to disclose CSR well is GCGwhich applied to the company.The purpose of this study was to determine the effect of CSR disclosure on company value and the role of GCG as moderation which supported by the inconsistency results of previous studies. Sample in this study were mining companies listed on the Indonesia Stock Exchange in 2013-2017 with a total of 33 companies. CSR was calculated using GRI G4 CSRDI, Tobin’s Q to measure company value and the GCG proxy was obtained by determining the highest score using the factor analysis method. Data analysis technique of this study uses Moderated Regression Analysis. Conclusions from the results of this study are that CSR disclosure has a negative effect on firm value, and GCG practices can strengthen the effect of CSR disclosure on Corporate Values ??in mining companies listed on the Stock Exchangeperiod 2013-2017. Keywords: CSR, company value, GCG